2012
DOI: 10.1155/2012/608269
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Penetrating Radar Investigations along Hajipur Fault: Himalayan Frontal Thrust—Attempt to Identify Near Subsurface Displacement, NW Himalaya, India

Abstract: The study area falls in the mesoseismal zone of 1905 Kangra earthquake (Mw 7.8). To identify appropriate trenching site for paleoseismic investigation and to understand the faulting geometry, ground-penetrating radar (GPR) survey was conducted across a Hajipur Fault (HF2) scarp, a branching out fault of Himalayan Frontal Thrust (HFT) in a foot hill zone of NW Himalaya. Several 2D and 3D profiles were collected using 200 MHz antenna with SIR 3000 unit. A 2D GPR profile collected across the HF2 scarp revealed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The Hajipur Fault shows 7.5 -8 m vertical displacement, a 7.6 + 1.7 mm a 21 slip rate and a 258 dip . Studies using ground-penetrating radar revealed that the dip of the Hajipur Fault varies substantially and that it has four splays (Malik et al 2012). Philip et al (2009) recognized the Panchbhaiya Thrust to be still active and referred to the NW-trending Rajban Thrust, possibly another out-of-sequence thrust sub-parallel to the Panchbhaiya Thrust.…”
Section: Himachal Pradesh Punjab and Haryana (India)mentioning
confidence: 99%
“…The Hajipur Fault shows 7.5 -8 m vertical displacement, a 7.6 + 1.7 mm a 21 slip rate and a 258 dip . Studies using ground-penetrating radar revealed that the dip of the Hajipur Fault varies substantially and that it has four splays (Malik et al 2012). Philip et al (2009) recognized the Panchbhaiya Thrust to be still active and referred to the NW-trending Rajban Thrust, possibly another out-of-sequence thrust sub-parallel to the Panchbhaiya Thrust.…”
Section: Himachal Pradesh Punjab and Haryana (India)mentioning
confidence: 99%
“…The study opened the possibility of three-dimensional GPR imaging of subsurface geological structures. Successive studies extended the approach to characterize active faults in different tectonic regimes combining 2D and pseudo-3D GPR surveys (e.g., Gross et al, 2002Gross et al, , 2003Gross et al, , 2004Green et al, 2003;Tronicke et al, 2006;McClymont et al, 2008McClymont et al, , 2009McClymont et al, , 2010Vanneste et al, 2008;Christie et al, 2009;Carpentier et al, 2012a, b;Malik et al, 2012;Brandes et al, 2018). A review of the near-surface GPR faulting studies suggests some reflection characteristics as possible indicators for the detection of subsurface fractures and faults (e.g., Smith and Jol, 1995;Liner and Liner, 1997;Reiss et al, 2003;Gross et al, 2004;McClymont et al, 2008and Bubeck et al, 2015.…”
Section: Methodsmentioning
confidence: 99%
“…CC BY 4.0 License. characterize active faults in different tectonic regimes combining 2D and pseudo-3D GPR surveys (Gross et al 2000(Gross et al , 2002(Gross et al , 2003(Gross et al , 2004Green et al 2003;Horstmeyer et al 2005;Tronicke et al 2006;McClymont et al 2008McClymont et al , 2009McClymont et al , 2010Vanneste et al 2008;Christie et al 2009;Carpentier et al 2012a,b;Malik et al 2012;Brandes et al 2018). A review of the near-surface GPR faulting studies suggests some reflection characteristics as possible indicators for the detection of subsurface fractures and faults (e.g.…”
Section: Methodsmentioning
confidence: 99%